Aetiologies and factors associated with poor clinical outcomes in rhabdomyolysis: a retrospective cohort study in an Australian trauma centre. Issue 2 (25th February 2021) - Khu, Yin Li; Lewis, Benjamin; Blackshaw, Lucinda; Tan, Suzanne May Quinn; Bayfield, Anna; Schneider, Hans Gerhard; Liew, Danny; Aung, Ar Kar
Abstract: Rhabdomyolysis is a clinical syndrome with significant morbidity and mortality that occurs as a result of traumatic and non‐traumatic aetiologies. Acute kidney injury, the need for dialysis, and death, can occur due to rhabdomyolysis. This study explores the aetiologies, clinical outcomes and associated factors for poor outcomes in a cohort of patients with rhabdomyolysis in a tertiary trauma centre in Australia.